ÐšÐ¾Ñ€Ñ€ÐµÐºÑ†Ð¸Ñ Ð¿Ð¾Ð¿ÑƒÐ»ÑÑ†Ð¸Ð¹ Ñ†ÐµÐ½Ð¾Ð±Ð¸Ð¾Ð½Ñ‚Ð¾Ð² Bifidobacterium spp. Ð¸ Lactobacillus spp. Ñƒ Ð¼Ñ‹ÑˆÐµÐ¹ Ñ ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ñ‹Ð¼ Ð´Ð¸ÑÐ±Ð¸Ð¾Ð·Ð¾Ð¼ ÐºÐ¸ÑˆÐµÑ‡Ð½Ð¸ÐºÐ° Ð¿Ð¾ÑÐ»Ðµ Ñ‚ÐµÑ€Ð°Ð¿Ð¸Ð¸ Ð¸Ð¼Ð¼Ð¾Ð±Ð¸Ð»Ð¸Ð·Ð¾Ð²Ð°Ð½Ð½Ñ‹Ð¼Ð¸ Ð½Ð° ÑÐ½Ñ‚ÐµÑ€Ð¾ÑÐ¾Ñ€Ð±ÐµÐ½Ñ‚Ð°Ñ… Ð¿Ñ€Ð¾Ð±Ð¸Ð¾Ñ‚Ð¸ÐºÐ°Ð¼Ð¸, Ñ…Ñ€Ð°Ð½Ð¸Ð²ÑˆÐ¸Ð¼Ð¸ÑÑ Ð¿Ñ€Ð¸ â€“80 Ð¸ â€“196Â°Ð¡ - Vysekantsev, Igor P.; Babinets, Olga M.; Martsenyuk, Valentina F.; Shatilova, Larisa Ye.; Scheglov, Andrey V.; Voyda, Yulia V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
The research revealed the recovery of the Bifidobacterium spp. and Lactobacillus spp. cenobiont populations in mucin of mice with experimental intestinal dysbiosis after treatment with free and immobilized on enterosorbents probiotics, stored for a year at a temperature of –80, –196°C. Experimental intestinal dysbiosis was simulated by Ampicillin and Metronidazole oral administration. Mice with induced dysbiosis were treated with free cells of S. boulardii, B. bifidum, L. bulgaricus probiotics, the mixtures of free cells with enterosorbents as well as the complexes of probiotic cells immobilized on enterosorbents. The enterosorbents based on activated carbon Sorbex and SCMS-1 were used. Immobilized probiotics have been found to provide a more rapid and complete recovery of cenobiont populations. Low-temperature storage for a year (observation period) and temperature storage regimen did not affect the therapeutic properties of free and immobilized cells of probiotics. The mechanisms of action of immobilized probiotics are under discussion.Probl Cryobiol Cryomed 2015; 25(3):267-286